2017
DOI: 10.1002/adfm.201605908
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Colorful Semitransparent Polymer Solar Cells with Ultrathin Hybrid‐Metal Electrodes and Fine‐Tuned Dielectric Mirrors

Abstract: Polymer solar cells (PSCs) possess the unique features of semitransparency and coloration, which make them potential candidates for applications in aesthetic windows. Here, the authors fabricate inverted semitransparent PSCs with high-quality hybrid Au/Ag transparent top electrodes and finetuned dielectric mirrors (DMs). It is demonstrated that the device color can be tailored and the light harvesting in the PSCs can be enhanced by matching the bandgap of the polymer donors in the active layer with the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
145
1
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 44 publications
0
145
1
1
Order By: Relevance
“…[165] Owing to the increase of the integrated photon flux density in the photoactive layer by 1DPCs, the PCE of 5.2% and J sc of 12.25 mA cm −2 were achieved, which were increased by 37% and 38%, respectively, when compared with those of the semitransparent devices without using 1DPCs. Very recently, Li et al [166] reported inverted semitransparent OSCs with Au/Ag TTE and fine-tuned dielectric mirrors (DMs) (see Figure 13c). The performance, reproducibility and colors of the inverted semitransparent OSCs can be significantly improved or tuned by integrating the DMs on the top of the devices.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[165] Owing to the increase of the integrated photon flux density in the photoactive layer by 1DPCs, the PCE of 5.2% and J sc of 12.25 mA cm −2 were achieved, which were increased by 37% and 38%, respectively, when compared with those of the semitransparent devices without using 1DPCs. Very recently, Li et al [166] reported inverted semitransparent OSCs with Au/Ag TTE and fine-tuned dielectric mirrors (DMs) (see Figure 13c). The performance, reproducibility and colors of the inverted semitransparent OSCs can be significantly improved or tuned by integrating the DMs on the top of the devices.…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…

protocols that tailor the absorption spectrum of the active material. This implies that the short-circuit current density, which is largely a function of the optical absorption, must be higher for a CF-integrated OPV compared to a transparent OPV, under the condition that the two devices show similar peak transmission efficiencies.The use of photonic structures as optical filters in OPVs or inorganic solar cells has been previously reported in the form of distributed Bragg reflectors, [7][8][9] photonic arrays, [10][11][12] and plasmonic resonators. Their use has also resulted in varied performances among devices of different colors, adding to the difficulty for practical implementation.

…”
mentioning
confidence: 99%
“…The use of photonic structures as optical filters in OPVs or inorganic solar cells has been previously reported in the form of distributed Bragg reflectors, [7][8][9] photonic arrays, [10][11][12] and plasmonic resonators. [13][14][15] While such filters enable various colors to be transmitted or reflected through tuning of the characteristic dimension of the filter components, in many cases they suffer from increased fabrication costs and duration because of the structural complexity.…”
mentioning
confidence: 99%
“…For practical applications, an average visible transmittance (AVT) of at least 25% in the blue–green–orange region is recommended . In the last decade or so, most of ST‐OSCs were consisted of polymer and FAs, with PCE of ≈8% even for tandem devices . Weakly absorbing FAs are partially responsible for the low PCE values.…”
Section: Other Aspects Of Frea Oscsmentioning
confidence: 99%